QSAR-analiz ostroĭ toksichnosti organicheskikh soedineniĭ pri peroral'nom vvedenii mysham - Tinkov, O V; Grigorev, V Yu; Polishchuk, P G; Yarkov, A V; Raevsky, O A (Biomeditsinskaia khimiia, 2019)
The effect of the structure of organic compounds on the acute toxicity upon oral injection in mice was studied using 2D simplex representation of the molecular structure and Random forest (RF) methods. Satisfactory quantitative structure-activity relationship (QSAR) models were constructed (R2 test = 0,61-0,62). The interpretation of the obtained QSAR models was carried out. The contributions of known toxicophores with established mechanisms of action were calculated in order to confirm the ability of the interpretation approach to correctly rank them relative to other structural fragments. The influence of the molecular surroundings of some toxicophores was analyzed. We analyzed the contributions of other highly ranked fragments from the list of common functional groups and ring systems in order to find new potential toxicophores. The on-line version of the expert system "OCHEM" (https://ochem.eu) and Arithmetic Mean Toxicity (AMT) approach were used for a comparative QSAR study.
Keywords: random forest; myši; QSAR; molekulární struktura; simplex descriptors; organické látky; testy akutní toxicity; Mice; Animals; molekulární modely; Molecular Structure; Toxicity Tests, Acute; zvířata; structure-property modeling; Administration, Oral; toxicity; Quantitative Structure-Activity Relationship; Organic Chemicals; structural interpretation; kvantitativní vztahy mezi strukturou a aktivitou; aplikace orální; Models, Molecular